2020
DOI: 10.3390/f11101051
|View full text |Cite
|
Sign up to set email alerts
|

Monochamus Saltuarius Endangers Pinus tabuliformis Carr. and Carries Bursaphelenchus xylophilus (Steiner and Buhrer) in China

Abstract: The pinewood nematode (Bursaphelenchus xylophilus) can cause fatal damage to trees and is transmitted by the vector species of the Monochamus genus. In December 2017, pinewood nematodes were found to be harming a large plot of pine trees, Pinus tabuliformis, in a new region with an average annual temperature of 6.7 °C in China. However, the vector insects were unknown and urgently needed to be identified. Hence, in April 2018, we collected wood sections of P. tabuliformis trees that had died from pine wilt dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…But then, the nematode has continuously adapted to low temperatures and has gradually expanded northward from tropical, subtropical, and south central warm‐temperate up to mid‐temperate climatic zone over recent years. As previously reported, M. saltuarius became the insect vector of B. xylophilus in Northeast China (Ge et al., 2021; Hou et al., 2021; Li et al., 2020; Pan, Li, et al., 2020). Though both the flight capacity (Zhang et al., 2007) and the number of nematodes carriage (Kobayashi et al., 1984; Pan, Li, et al., 2020; Zhan et al., 2014) were relatively weaker for M. saltuarius than M .…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations
“…But then, the nematode has continuously adapted to low temperatures and has gradually expanded northward from tropical, subtropical, and south central warm‐temperate up to mid‐temperate climatic zone over recent years. As previously reported, M. saltuarius became the insect vector of B. xylophilus in Northeast China (Ge et al., 2021; Hou et al., 2021; Li et al., 2020; Pan, Li, et al., 2020). Though both the flight capacity (Zhang et al., 2007) and the number of nematodes carriage (Kobayashi et al., 1984; Pan, Li, et al., 2020; Zhan et al., 2014) were relatively weaker for M. saltuarius than M .…”
Section: Discussionmentioning
confidence: 54%
“…As previously reported, M. saltuarius became the insect vector of B. xylophilus in Northeast China (Ge et al., 2021; Hou et al., 2021; Li et al., 2020; Pan, Li, et al., 2020). Though both the flight capacity (Zhang et al., 2007) and the number of nematodes carriage (Kobayashi et al., 1984; Pan, Li, et al., 2020; Zhan et al., 2014) were relatively weaker for M. saltuarius than M . alternatus , M. saltuarius represented the main dispersal vector endemic to the mid‐temperate zone of China which has small or no M .…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…In 2017, thousands of Korean pines that had died due to PWD were reported in northeastern China, and it was revealed that PWD was caused by PWN, which was vectored by M. saltuarius in northeast China [ 8 ]. M. saltuarius emerged from P. tabuliformis carried pine wood nematode and its carrier rate reached 58.3%, and the average carrying capacity of M. saltuarius of pine wood nematodes was 642.4 [ 9 ].…”
Section: Introductionmentioning
confidence: 99%